The dilemma and future of property valuation education in China. (3rd May 2016) - Xiao, Yan; Chan, Nelson
Abstract: Foreign fund investments in China create demand for real estate appraisal for foreign investment projects, and they expect to have quality valuation services. The majority of real estate appraisers in China are not familiar with the needs and requirements of foreign clients. Apart from technical capabilities, they are not good at writing English appraisal reports. It is difficult for them to compete with international appraisers. The core of the problems lies in real estate education in China. This paper aims to study the current condition and the gap in real estate education between China and selected foreign countries, and subsequently recommend what need to be done to raise the level of Chinese real estate education and hence appraisers to meet the expectations of international clients. The study finds that while raising the level of Chinese real estate appraisal education to match the selected countries is possible, there is a long way to go.